Neighborhoods of certain analytic functions with negative coefficients - Osman Altintas; Shigeyoshi Owa (International Journal of Mathematics and Mathematical Sciences)
The object of the present paper is to derive some properties of neighborhoods of analytic functions with negative coefficients in the open unit disk.